1985
DOI: 10.1055/s-2007-969580
|View full text |Cite
|
Sign up to set email alerts
|

New Furoacridone Alkaloids from Tissue Culture ofRuta graveolens

Abstract: Two new furacridone alkaloids have been obtained from tissue culture of RUTA GRAVEOLENS by DCCC of a crude dichloromethane extract and subsequent CC and TLC. On the basis of spectroscopic data their structures have been determined to be 1-hydroxyrutacridone epoxide ( 3) and its intramolecular substitution product ( 5, rutagravin); a third furoacridone has been identified as gravacridonol ( 4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The results of the bioassay indicated that 2 was 100· less active than 1 against O. perornata (Table 1). Both compound 2 and its possible biosynthetic precursor 1 have been previously isolated from R. graveolens Reisch et al, 1976;Baumert et al, 1987;Nahrstedt et al, 1981Nahrstedt et al, , 1985. Rutacridone (3), a possible biosynthetic precursor of compound 2, was isolated from the same extract and had no activity in this bioassay.…”
Section: Resultsmentioning
confidence: 88%
“…The results of the bioassay indicated that 2 was 100· less active than 1 against O. perornata (Table 1). Both compound 2 and its possible biosynthetic precursor 1 have been previously isolated from R. graveolens Reisch et al, 1976;Baumert et al, 1987;Nahrstedt et al, 1981Nahrstedt et al, , 1985. Rutacridone (3), a possible biosynthetic precursor of compound 2, was isolated from the same extract and had no activity in this bioassay.…”
Section: Resultsmentioning
confidence: 88%
“…Hierbei gilt besonderes Interesse den Epoxiden von Acronycin (1) und Rutacridon, sowie den entsprechenden Folgeprodukten nach Hydrolyse. In unserer Arbeitsgruppe [3], [4], [5], [6] ftihrten umfangreiche Oxidationsversuche unter anderem zu dem aus Ruta graveolens isolierten Naturstoff Rutagravin [7], sowie zu einem potentiellen Naturstoff Dihydrohallacridon [8], vermutlich eine biosynthetische Vorstufe von Hallacridon [9]. Die Synthese von Dihydrohallacridon und Rutagravin erfolgte durch Oxidation von Rutacridon mit Kaliumpermanganat [4].…”
unclassified
“…After preparative HPLC the mass spectrum showed the following peaks at m/z 323 (M +) 306, 294, 292, 278, 265, 241. The 2H NMR spectrum was fully in accord with that of gravacridonol [7,12]. Especially informative are the two two-proton signals at 5.3 and 4.3 ppm showing the presence of a hydroxymethylethenyl group.…”
Section: Resultsmentioning
confidence: 55%